The given expression can be simplified to: 3b-a
p=b+3a+c p-3a-c=b+3a-3a+c-c p-3a-c=b b=p-3a-c
If a + b = 6, what is the value of 3a + 3b?
3a+ax+3b+bx = 3(a+b)+(a+b)x = (a+b)(3+x)
They are terms of an algebraic expression
This expression can be factored. ab + 3a + b2 + 3b = a(b + 3) + b(b + 3) = (a + b)(b + 3)
It is simply as stated in the question. Without information about a or b, the expression cannot be simplified nor evaluated.
3ab + 3ac + 2b2 + 2bc = 3a(b + c) + 2b(b + c) = (3a + 2b)(b + c)
= a + b - 2
-2a plus 3b
Collect the terms in a, then the terms in b, getting 6a - 3a + 2b + 5b which simplifies to 3a + 7b. Gettit?
What is the answers to -7 ( a + b - 5 ) + 8 ( -3a +2b ) + b ( 7 + 3 )
a = 15.
6a square plus b square
That factors to (b + 3)(a + c)
(x + 3)(a + b)
7a minus 2, if "3a-2" means 3a minus 2. 3a plus 1 and 1-3rd in parenthesis times 3a, if "3a-2" means 3a squared. a plus 3a squared plus 3a = 1-3rd times 3a plus 3a times 3a plus 1 times 3a = 3a plus 1 and 1-3rd in parenthesis times 3a
(b + 3)(a + c)
5a + 4b - 3a =(5a - 3a) + 4b =2a + 4b =2 (a + 2b)
It is: 5(3a+b) when factored